Morphological and Molecular Identification of Fungi Isolated From Selected Brri Rice Varieties - Nishi, Habiba Rashid; Shamsi, Shamim; Noman, Md Abdullah Al (Bangladesh Journal of Plant Taxonomy, 2024)
A total of 19 fungal species were isolated from the seeds of selected rice varieties (BRRI dhan 90 to BRRI dhan 99) following Tissue planting method and Blotter method. The isolated fungi were Aspergillus niger, A. ochraceus, A. oryzae, A. tamarii, A. terreus, Chaetomium globosum, Cladosporium oxysporum, Colletotrichum gloeosporioides, Corynespora cassiicola, Curvularia lunata, Curvularia soli, Daldinia eschscholtzii, Fusarium solani, Penicillium oxalicum,Penicillium sclerotiorum, Pestalotiopsis guepinii, Pyricularia oryzae and Rhizopus stolonifer. Fourteen fungi were selected for molecular identification. Out of the 19 fungal isolates, 14 were confirmed up to species level through ITS sequence based molecular analysis. Among the isolated fungi Pnicillium sclerotiorum and Curvularia soli are the new record for Bangladesh. Association of Daldinia eschscholtzii with rice seeds is also recorded first time from world. Bangladesh J. Plant Taxon. 31(1): 73-82, 2024 (June)